Environmental journalism and Citizenship: notes on burning in the Amazon (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article aims to reflect on the speeches present on the covers of the newspapers Estado de Minas and Extra about the fires that occurred in the Amazon region in August 2019. In this sense, based on the principles of environmental journalism and the events, the information gained repercussions, with a provocative and questioning potential of how public agents and citizens relate to the environment. From the textual discursive analysis, we show that the analyzed journals bring elements that problematize the relationship between human beings and environmental issues and encourage them to change behaviors in a conscious and engaged manner.
Keywords: Environment; Amazon; Environmental journalism; Discourse analysis; Fires